Teaching Professionalization In Vulnerable Contexts: Strategy To Promote Educational Quality And Inclusion In Mexico - de Jesús Mapén Franco, Fabiola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of the research is to determine the impact of the training programs offered by the educational authorities in 2021, in the state of Tabasco, Mexico, on basic education teachers who work in vulnerable contexts. The importance of the study is understood since it is a strategy that the Mexican State applies to promote educational quality and inclusion. The approach is quantitative, the validation and reliability of the instrument was carried out through expert judgment and a Cronbach’s alpha of 0.92. The results obtained provided relevant information related to academic and technological aspects.